The Comparison of Non-Silver-Based Treatment vs Silver-Based Treatment in Pediatric Burns: Meta-Analysis and Systematic Review - Yatindra, Ida Ayu Cempaka Dewi; Rooseno, Ratna Rayeni Natasha; Tiaraningrum, R.Ratu Kania; Dharmawan, Made Surya (Bali Medical and Wellness Journal, 2024)
Background: Pediatric burn injuries are a significant global concern, caused by factors such as child maltreatment, fire accidents, and scalding. Effective treatment aims to enhance wound healing and re-epithelialization. Silver-based treatments are a standard approach for burn wounds, but new alternatives may offer improved outcomes. Objective: This study conducts a meta-analysis and systematic review to compare silver and non-silver treatments in pediatric burn care. Methods: A comprehensive literature review and meta-analysis were conducted using the PRISMA guidelines. Data from PubMed, Cochrane Library, and ScienceDirect were utilized. The study focused on children with burn injuries, comparing non-silver treatments (intervention) against silver treatments (control) and assessing outcomes like wound healing, dressing frequency, hospital stay length, complications, graft needs, and pain. Results: The review included 12 randomized controlled trials with 719 participants. Silver treatments served as controls against various non-silver options. Although many trials showed bias and varied quality, results indicated that non-silver treatments led to faster wound healing (mean difference: -0.86 days; 95% CI: −1.26, −0.46; p < 0.0001), fewer dressing changes (mean difference: -2.07 times; 95% CI: -3.39, -0.75; p = 0.0002), and reduced hospital stays (mean difference: −0.76 days; 95% CI: −1.57, 0.05; p = 0.07). No significant differences were found in infection rates or graft needs. Conclusion: Non-silver treatments in pediatric burns result in faster healing, fewer dressings, and shorter hospital stays compared to silver treatments. Further large-scale studies are necessary to confirm these findings.